Role of irradiation in combined treatment of head and neck paragangliomas at the Centre of Oncology in Krakow between 1970–2005 - Pęcak, Magdalena; Pluta, Elżbieta; Hetnał, Marcin; Wróbel-Radecka, Renata; Szadurska, Agnieszka; Brandys, Piotr; Kukiełka, Andrzej; Dąbrowski, Tomasz; Walasek, Tomasz; Skołyszewski, Jan (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study is to evaluate the results of postoperative radiotherapy of paragangliomas, prognostic factors and causes of treatment failure. Material and methods : Forty-four patients (39 females and 5 males) aged 20 to 74 years were treated for paraganglioma between 1970 and 2010 at the Centre of Oncology in Kraków. Patient survival probability was estimated with the Kaplan-Meier method. Log-rank tests and Cox proportional hazard model were used in univariate and multivariate analysis, respectively. Results: The most common locations of paragangliomas were the following: the ear, carotid body and internal jugular vein bulb. Forty (91%) out of them were benign and 4 – malignant. All patients underwent surgery followed by adjuvant radiotherapy. The delivered dose ranged from 50 to 72 Gy, the mean dose was 60 Gy. Five-year overall survival was 84%. Five-year relapse-free survival was 84%, either. The multivariate analysis has shown that the dose in an independent prognostic factor for the overall survival. The univariate analysis has shown significantly higher 5-year overall survival in patients who received a dose of 60 Gy or higher – 92% vs. 70% in patients who received a dose lower than 60 Gy. Conclusions : Postoperative radiotherapy with doses higher than 60 Gy in patients with paragangliomas is associated with longer overall survival.